Hearing the Old Testament in the New Testament - Porter, Stanley E. (McMaster New Testament studies, 2006)
How does the New Testament echo the Old? Which versions of the Hebrew Scriptures were authoritative for New Testament writers? The appearance of concepts, images, and passages from the Old Testament in the books of the New raises important questions about textual versions, allusions, and the differences between ancient and modern meaning. Presenting essays from a range of distinguished scholars, "Hearing the Old Testament in the New Testament" begins by laying out the foundational issues and then investigates the use of the Old Testament in specific segments of the New Testament. A concluding chapter by Andreas Kostenberger both questions and affirms the previous contributors' findings, offering much-needed direction for further inquiry into this vital area of biblical study.